Investigating climate resilience initiatives among Malaysian takaful operators - Che Mohd Salleh, Marhanum; Ramli, Riwan; Sarabdeen, Masahina (Nova Science Publishers, Inc., 2026)
Despite the recent growth of climate risk insurance markets globally, most approaches to climate risk protection are based on conventional insurance. As an Islamic insurance, Takaful should be at the forefront of catering to this special segment of risk, given its unique nature to support society in the face of unexpected events. It has been observed that sustainable initiatives for climate resilience are still lacking in the Takaful industry. This research, therefore, investigates the climate resilience initiatives among Malaysian Takaful operators in both Family and General Takaful businesses. This objective is achieved through a qualitative approach, wherein a review of websites and annual reports reveals initiatives undertaken by Family and General Takaful operators to support climate resilience or Environmental, Social, and Governance (ESG) activities. Through critical observation, it has been found that, in terms of products, most General Takaful operators have included climate resilience protection in their offerings as an additional rider to basic coverage. These include Motor Takaful, Fire Takaful, Householder Takaful, and Houseowner Takaful. In contrast, none of the Family Takaful operators offer protection against climate change in their products. However, three of them provide ESG funds for their investment-linked products. Overall, other initiatives aimed at climate resilience occur at the group level. The results of this research would provide valuable insights for the Takaful industry in identifying gaps and needs to offer specialised products that cater to the protection of communities relying on highly vulnerable sectors affected by climate risks, such as agriculture, livestock, fishing, forestry, and tourism. This segment has received less attention from the Takaful industry and primarily comprises underprivileged communities in rural villages. The availability of affordable Takaful products to mitigate risks related to climate change would hold great significance for this group.